Pengembangan Sistem Pengelolaan Transaksi Keuangan dan Persediaan Barang Toko Kosmetik Berbasis Desktop (Studi Kasus: Rumah Melati Bandung) - Rizdiani Tri Prastiti; Denny Sagita Rusdianto; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Rumah Melati is a cosmetics store located in Bandung. In order to develop an adequate store business, a good financial and product management is required. However, this store haven't met those requirements. The store not yet have automatic record of any transaction, therefore the supply list is remain unclear and often leads to miscalculation of the supply itself. Cosmetic products has an expiration date that needs to be regularly noted so that no products would be wasted and creates an imbalance in financial report. Rumah Melati's system is not enticing enough to the costumers. If these problems are not be overcome in no time, the store would face a bankruptcy. To overcome these problems, a Development of Desktop-Based Financial Transaction and Supply Management System in Cosmetics Store is, in fact, needed to manage the sales transactions, supply, expiration date information, financial report, promotion, and membership system. This research started with requirement engineering which analyzed to 36 functional requirements and 1 non-functional requirement. Based on that, design and implementation are conducted. Implementation is conduct using Java Programming Language with Model View Controller (MVC) design pattern and MySQL database. Afterward, unit testing; integration testing; validation testing are conducted which result complexity number under 10 and 100% valid. In the sequel, usability testing resulted in score of 82.5 which means the system is categorized as excellent.